2012
DOI: 10.1007/s00586-012-2410-0
|View full text |Cite
|
Sign up to set email alerts
|

Progressive thoracic myelopathy caused by spinal calcium pyrophosphate crystal deposition because of proximal junctional vertebral compression fracture after lumbopelvic fusion

Abstract: Purpose We describe cases presenting with progressive thoracic myelopathy after lumbopelvic fusion attributed to proximal junctional vertebral compression fracture (PJF) followed by spinal calcium pyrophosphate dehydrate (CPPD) crystal deposition. Methods The study included six patients, ranging from 62 to 75 years. All patients had been treated previously with lumbopelvic fusion. The mean period from the detection of PJF to the onset of myelopathy was 4.8 months. Notably, five patients demonstrated upper-inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…1,2 By contrast, UIV fractures among PJFs can sometimes lead to the need for reoperation and severe symptoms. 7,8 Oe et al reported that 58 (18.2%) of 318 patients who underwent ASD surgery suffered UIV fractures within 1 year. 9 The mean UIV level was T9 (+2) in both the UIV fracture and non-fracture groups with no significant difference therefore, it is very important to prevent UIV fractures.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 By contrast, UIV fractures among PJFs can sometimes lead to the need for reoperation and severe symptoms. 7,8 Oe et al reported that 58 (18.2%) of 318 patients who underwent ASD surgery suffered UIV fractures within 1 year. 9 The mean UIV level was T9 (+2) in both the UIV fracture and non-fracture groups with no significant difference therefore, it is very important to prevent UIV fractures.…”
Section: Discussionmentioning
confidence: 99%
“…That same year, Odate et al reported 6 cases of adjacent-segment CPPD deposition following thoracolumbopelvic fixation. 19 In all cases, the CPPD involvement was within or immediately adjacent to the surgical site, diagnosed by identification of CPPD and multinucleated giant cells within the liga-mentum flavum removed during the subsequent decompressive laminectomies. In contrast to these reports, in the present case the patient developed pseudogout at levels remote from the lumbar fusion, involving both cervical and thoracic elements.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear what role these previous surgeries had in the development of CPPD. Although local trauma is a known risk factor for CPPD [39][40][41][42], our patient presented eight years after his previous spine surgeries. Ogawa et al reported the first case of acute lumbar spinal pseudogout occurring four weeks after spinal instrumentation [39] .…”
Section: Discussionmentioning
confidence: 87%